Sofrimento Psíquico e o Trabalho - Barbosa, Irella Borges dos Santos (2018)
This research is part of the Society for Education and Research (TSE) Research Line of the Postgraduate Program in Education (PPGED) of the Faculty of Education of the Federal University of Uberlândia and was supported by FAPEMIG. It starts from the need to carry out a sociological analysis and from the field of psychodynamic psychology, with a psychoanalytical approach, with a view to discussing how work is organized in our society and its reflexes in the psychological suffering of the worker in general. As a pretension, it was intended to contribute to the debate about the prevention of psychological suffering in the working class. Our purpose is to reflect on the history of the construction of Psychology, as well as to construct a historical narrative about psychology as a science, together with the influences of philosophical thought of the constitution and basis for a better understanding: at the service of what or from whom psychological science constructs its discourse; to know and present data that demonstrate the physical and psychological illness and its possible relations with the psychological suffering of workers, to know and to present modes of manifestations of psychic sufferings of workers according to the literature and finally present reflection on the work, the worker and their socioeconomic conditions, as well as the psychosocial influences under which the subject is placed. For that, the categories Labor and Human Suffering with theoretical foundation are used in Marx (2013), Antunes (2015), Arendt (2007); Santos (2003), Birman (2014), Brant (2017), Braverman (1981), Dejours (2013), Foucault (1988), Freud (1930), Cruxên (2004), Lacan (2008) Aranha (1989) and Cuéllar (2010). The methodology adopted was the bibliographical and documentary research in primary and secondary sources. It starts from the premise that the psychic suffering of the worker is a cut within the immeasurable universe of the world of work. It is a negative reflection of the kind of dehumanized relation that happens to exist between the individuals within a socioeconomic system prevailing in certain societies, in a certain historical time and disseminated in organizations of work throughout the world. The results presented in this research allow us to infer that the precarization of work dehumanizes man and his relationships, interfering in a violent way in the way of being and acting of individuals. Due to the importance that work occupies in the development of human life as a whole - both in the social aspects that constitute the subjects' identity and in the psychic aspects related to the constructions of meaning that each individual realizes about his / her doing - it becomes indispensable the theme for those who want to know a little more about the human being.